2019
DOI: 10.1152/japplphysiol.00341.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss on dynamic hyperinflation in obese women asthmatics

Abstract: Obese adults with asthma are more likely to develop dynamic hyperinflation (DH) and expiratory flow limitation (EFL) than nonobese asthmatics, and weight-loss seems to improve the breathing mechanics during exercise. However, studies evaluating the effect of weight loss on DH in obese adults with asthma have not been performed. We sought to evaluate the effect of a weight loss program on DH in obese adults with asthma. Forty-two asthma patients were enrolled in a weight loss program (diet, psychological suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Thus, more studies are required to explore the interaction between CPAP and leptin levels in OSA patients. Remarkably, weight loss is the effective therapy way for OSA and asthma [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more studies are required to explore the interaction between CPAP and leptin levels in OSA patients. Remarkably, weight loss is the effective therapy way for OSA and asthma [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…After a thorough evaluation of the full-text papers, we ultimately included five papers in the final analysis, consisting of prospective analysis, cross-sectional study, retrospective analysis, experimental study, and secondary analysis to a randomized control trial. In a 2019 prospective study by Silva et al 4 , 51 initially enrolled patients faced various challenges leading to a final cohort of 42 asthma patients. These participants were categorized into two groups, based on their weight loss achievements: those with ≥5% weight loss (n = 19) and those with <5% weight loss (n = 23), exhibiting similar baseline characteristics before the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Following the intervention, the ≥5% group experienced a significant increase in tidal volume, with no significant difference in respiratory rates between the two groups. 4 Before the intervention, both groups exhibited similar health-related quality of life (HRQoL) and asthma control. However, the ≥5% group demonstrated substantial improvements in all domains of the Asthma Quality of Life Questionnaire (AQLQ) and the Asthma Control Questionnaire (ACQ) post-intervention, with significant differences in AQLQ domains related to activity limitations, symptoms, and total scores.…”
Section: Resultsmentioning
confidence: 99%
“…The authors correctly question the generalisability based on these limitations. Grandi Silva et al [32] reported a trial of weight loss (nutritional support, psychology input and a varied exercise programme) in women with BMI 35-40kg/m 2 and moderate-to-severe asthma (n=51) to assess the effect on dynamic hyperinflation. Post-hoc analysis showed improvements in ACQ and AQLQ in those that lost 5% weight, though no significant change in ACQ when compared to those that lost <5%.…”
Section: Discussionmentioning
confidence: 99%